2022
DOI: 10.1177/15910199221089766
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of n-butyl cyanoacrylate compared with ethylene vinyl alcohol copolymer liquid embolic embolization of brain arteriovenous malformations (bAVMs) from a US hospital perspective

Abstract: Background In US hospitals, the liquid embolic systems (LESs) n-butyl cyanoacrylate (n-BCA) and ethylene vinyl alcohol copolymer (EVOH) are used for brain arteriovenous malformation (bAVM) embolization to achieve presurgical devascularization. The aim of this study was to perform an economic analysis comparing four techniques for bAVM embolization based on LES, ancillary device, and angiography suite time costs. Methods An economic model was developed comparing the embolization costs for n-BCA, EVOH with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A recently published economic model, leveraging a clinician-verified clinical scenario, compared costs associated with the required LES units and ancillary devices, as well as the procedural time differences between TRUFILL using a 3:1 dilution and three techniques using Onyx. 7 The study concluded that the use of TRUFILL resulted in the use of fewer devices and shorter procedure time compared to any of the Onyx techniques examined. Higher costs were driven by additional units of Onyx as well as additional or specialty microcatheters needed for deployment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recently published economic model, leveraging a clinician-verified clinical scenario, compared costs associated with the required LES units and ancillary devices, as well as the procedural time differences between TRUFILL using a 3:1 dilution and three techniques using Onyx. 7 The study concluded that the use of TRUFILL resulted in the use of fewer devices and shorter procedure time compared to any of the Onyx techniques examined. Higher costs were driven by additional units of Onyx as well as additional or specialty microcatheters needed for deployment.…”
Section: Discussionmentioning
confidence: 97%
“…Higher costs were driven by additional units of Onyx as well as additional or specialty microcatheters needed for deployment. 7 Clinical outcomes including safety, efficacy, and effectiveness in studies comparing TRUFILL and Onyx in treating patients with bAVMs have been widely assessed in the literature, and collectively show similar outcomes regarding safety and bAVM obliteration. 5,6,12,13 Interestingly, studies providing direct comparisons of the costs associated with TRUFILL and Onyx in treating patients with bAVM are scarce, and costs must be inferred from procedural characteristics and resource utilization.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation